Factors Influencing the Incidence of Stunting in the Working Area of UPTD Puskesmas Bukit Gadeng, Kota Bahagia District, South Aceh Regency - Sudana Fatahillah Pasaribu; Tuty Hertati Purba; Sadikhah Sadikhah; Bety Agustina Rahayu; Sarni Anggoro (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
One of the nutritional problems that occur in children under five is stunting, also known as chronic nutritional problems due to insufficient fulfillment for long periods of time. A child under five is considered to have stunted nutritional status if his height is less than minus two median standard deviations of the World Health Organization (WHO) growth standards. Stunting is caused by direct causes, namely nutritional intake, infectious diseases, exclusive breastfeeding, indirect causes, namely sanitation, education, parental knowledge, income, number of family members, resources, technology, and the environment. This study aims to determine the factors that affect the incidence of stunting. This study aims to determine the factors that affect the incidence of stunting. This type of research is observational research analytic case control approach. The research samples were 49 stunted children (case Group) and 49 children without stunting (control group) in the working area of Bukit Gadeng Public Health Center, Bahagia District, South Aceh Regency, Aceh province. The Data were analyzed by performing Chi-square analysis test and the value of (OR) Odds ratio. The results showed a significant value of maternal knowledge (p-value=0.00); (OR=72.45), environmental sanitation hygiene (p-value=0.001); (OR= 2.14), history of exclusive breastfeeding (p-value=0.00); (OR= 19.37), history of infectious diseases (p-value=0.064); (OR= 3.45). Conclusion maternal knowledge, environmental sanitation hygiene, and history of exclusive breastfeeding affect the incidence of stunting and infectious disease history does not affect the incidence of stunting in the Bukit Gadeng Public Health Center, Bahagia District, and South Aceh Regency. Knowledge, sanitation hygiene, and Exclusive, breastfeeding, affect the incidence of stunting and infectious disease does not affect the incidence of stunting in the Bukit Gadeng Public Health Center, Bahagia District, and South Aceh Regency.